Avaliação de pavimentos flexíveis utilizando o método IGG - Índice de Gravidade Global. Estudo de caso: Av. Caubi Sérgio Melo localizada no bairro Renascer em Macapá-AP - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2024)
This study discusses paved roads, their concepts, functionalities, and importance, with a focus on the application of the Global Severity Index (GSI) – a method standardized by DNIT (006/2003) for evaluating flexible and semi-rigid pavements. Road transport is extremely important for the country's economy and mobility, as it is responsible for 60% of freight and 90% of passenger transportation. However, road infrastructure faces issues such as lack of investment in maintenance and/or rehabilitation, directly impacting user safety and comfort. The applied methodology (GSI) aims to identify pavement defects and determine their severity, allowing for a targeted action plan to address identified defects and adopt more efficient strategies for problem resolution, thereby maximizing the use of available resources. In the study conducted, the GSI method was used to evaluate the conditions of Av. Caubi Sérgio Melo in Macapá-AP, an important road connecting several neighborhoods. The results indicated that the road is in a functionally poor condition. Considering the functional state and decision making parameters, resurfacing is a potentially recommended solution for the section, enabling a corrective action proposal to extend the pavement's useful life. In other words, this method contributes to the durability of the road network and provides a better return on infrastructure investment, ultimately improving the quality of road transport in the country.
Keywords: Pavimentação urbana - Macapá (AP); Pavimentação asfáltica - Patologia; Índice de Gravidade Global (IGG); Avaliação de pavimentos; CNPQ::ENGENHARIAS::ENGENHARIA CIVIL::INFRA-ESTRUTURA DE TRANSPORTES::RODOVIAS; PROJETO E CONSTRUCAO